The inclusion of green chemistry in postgraduate programmes in Chemistry in Brazil: trends and perspectives - Zuin, Vânia Gomes (2014)
This article aims at investigating ways in which the principles of Green Chemistry are included in Brazilian postgraduate programmes in Chemistry. It assumes that, in the face of today’s challenges concerning the production of knowledge and the formation of human resources focused on social and environmental sustainability, it has become necessary to reflect on topics, proposals, potentialities and limits related to Green Chemistry, which occurs in the courses offered in over 40 postgraduate programmes in Chemistry in the country. It is possible to observe that almost all of such topics include disciplines, groups, research lines and projects for development, analysis and formation which permit the rethinking of ways of creating green materials and processes in the contemporary Brazilian academic context.